Roma Childhood in Eastern Europe - Kozma, Tamas; Pusztai, Gabriella; Tarkos, Katalin (Acta Paedagogica Vilnensia, 2003)
This paper illustrates the problems of Roma children through the life of a particular group of emigrants, and looks for the answer how much their ambition, that is behind the undertaking of the emigrants, supported their adaptation to a new social environment. European literature has not really dealt with the emigration of this ethnic group until this time because during the existence of the "iron curtain" until 1990 the migration directed from the east towards the west did not have large dimensions except during the big political upheavals. Ongoing research demonstrates a region called the "Partium" that is suitable for representing the whole area like a drop in the sea because of its mixed ethnicity. Then this paper shows the present situation of the Gypsies in this region, the background of Gypsy children’s school failures and at last gives a case study on an emerging class of the Gypsies and their problems. During the empirical analysis the method of network analysis is also used that seema as an adequate approach of researches dealing with social integration of immigrants according to the intemational literature (Kelly & Portes, 1993).